Bisphenol A migration from plastic materials: direct insight of ecotoxicity in Daphnia magna - Mansilha, Catarina (2014)
Bisphenol A (BPA) is an endocrine disrupting chemical (EDC) whose migration from food packaging is recognized worldwide. However, the real overall food contamination and related consequences are yet largely unknown. Among humans, children’s exposure to BPA has been emphasized because of the immaturity of their biological systems. The main aim of this study was to assess the reproductive impact of BPA leached from commercially available plastic containers used or related to child nutrition, performing ecotoxicological tests using the biomonitoring species Daphnia magna. Acute and chronic tests, as well as single and multigenerational tests were done. Migration of BPA from several baby bottles and other plastic containers evaluated by GC-MS indicated that a broader range of foodstuff may be contaminated when packed in plastics. Ecotoxicological test results performed using defined concentrations of BPA were in agreement with literature, although a precocious maturity of daphnids was detected at 3.0 mg/L. Curiously, an increased reproductive output (neonates per female) was observed when daphnids were bred in the polycarbonate (PC) containers (145.1±4.3 % to 264.7±3.8 %), both in single as in multigenerational tests, in comparison with the negative control group (100.3±1.6 %). A strong correlated dose-dependent ecotoxicological effect was observed, providing evidence that BPA leached from plastic food packaging materials act as functional estrogen in vivo at very low concentrations. In contrast, neonate production by daphnids cultured in polypropylene and non-PC bottles was slightly but not significantly enhanced (92.5±2.0 % to 118.8±1.8 %). Multigenerational tests also revealed magnification of the adverse effects, not only on fecundity but also on mortality, which represents a worrying trend for organisms that are chronically exposed to xenoestrogens for many generations. Two plausible explanations for the observed results could be given: a non-monotonic dose–response relationship or a mixture toxicity effect.